Simbiótico e extratos naturais na dieta de codornas Japonesas na fase de postura - Da Silva, Janaina Della Torre [UNESP]; Matos, Alexandra Da Silva [UNESP]; Hada, Fabricio Hirota [UNESP]; Gravena, Rodrigo Antonio [UNESP]; Marques, Rafael Henrique [UNESP]; Moraes, Vera Maria Barbosa [UNESP] (FapUNIFESP (SciELO), 2012)
The objective of this study was to assess the performance, tonic immobility time (TIT), intensity of injuries (II) and heterophil to lymphocyte ratio (H:L) by the addition of the symbiotic and plant extract (Aloe vera and Symphytum officinale) to the diet of Japanese quails. Ninety quails were used, distributed in randomized blocks with 3 treatments (0-control; 250 and 750 mg symbiotic and plant extract/kg of diet), five repetitions and six birds per cage. Feed intake, feed conversion, production and weight of eggs, viability, TIT, II and H:L were evaluated. Results showed that the addition of the product to the diet did not affect the performance, however, it decreased the TIT, II and the H:L of quails which received the highest level of the product in the diet. Thus, the use of symbiotic and plant extract in the diet has been promising regarding the behavioral and physiological parameters, decreasing the stress of the animals, mainly for the level of 750 mg/kg diet.
Symbiotic and natural extracts in diets for Japanese quails at laying period
Keywords: Aloe vera; Coturnix coturnix japonica; Prebiotic; Probiotic; Symphytum officinale L.; Animalia; Aves; Coturnix; Coturnix japonica; Phasianidae; Symphytum; Symphytum officinale